Analysis of the impact of information in a digital environment on a person by media psychological methods - Kutym Л.Қ. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The growth of technological capabilities of information and communication tools exacerbated their negative impact on humans. Scientific and technological progress has accelerated the spread of information, changed its quality and content. Humanity has gone through several technological stages in its history. The article analyzes the nature of the stages and breakthroughs characterized by historical and socio-economic criteria. The latest digital tools, discoveries in biotechnology, artificial intelligence determine the direction of human progress. The author focuses on the study of the credibility of these findings. He proposes a hypothesis that technological advancement may exacerbate social, cultural, and spiritual problems. Scientific concepts that determine the mechanisms of effective influence on human consciousness have been emerged. The mass media are constantly improving psychological tools in order to increase the impact on the audience and advertising revenues. The article analyzes both the opportunities and the threats that technological progress provides. The negative impact on children and adolescents of a large flow of negative information is growing. The author concludes that the state and society should jointly fight against modern challenges in the information environment.